ANALISIS PERBANDINGAN BEKISTING KONVENSIONAL DENGAN BEKISTING SISTEM PERI PADA GEDUNG BERTINGKAT - Ulum, Muhammad Miftakhul; Adi, Henny Pratiwi; Ni'am, Moh Faiqun (UNISSULA Semarang, 2024)
Formwork is a tool to help mold concrete with the desired size, shape, or position. In the implementation of formwork work, the selection of the type of formwork will affect the cost, implementation time, and construction quality. There are 3 (three) types of formwork in Indonesia, including conventional formwork, semi-system formwork, and system formwork. In this study, the installation and dismantling methods of conventional formwork and PERI System formwork will be analyzed, a comparison of the calculation of time and costs required for the installation and dismantling of conventional formwork with PERI system formwork in 3 different buildings, and an analysis of the economic feasibility study of PERI system formwork investment.This research is a quantitative research with the aim of knowing the comparative analysis of conventional formwork methods and PERI system formwork, then analyzing the material requirements and costs between conventional formwork and PERI system formwork and conducting an investment feasibility study analysis of the PERI System formwork. The work reviewed is on plate and beam work.The results of the study showed that the cost of procuring PERI System formwork was Rp 6,181,415,050 more expensive than conventional formwork. In the implementation of the installation and dismantling of PERI system formwork, it was faster than conventional formwork, the difference in installation production capacity was 6 m2/day, while the difference in dismantling time was 2m²/day. The investment feasibility study for the procurement of PERI System formwork is still feasible because the Net Present Value (NPV) value obtained was Rp 63,801,026, the Benefit Cost Ratio (BCR) value obtained was 1.007 and the Internal Rate Of Return (IRR) value was 9.48%.Keywords : Formwork, Conventional, PERI System, Investment Feasibility.